Artificial Intelligence: A New Paradigm in Human Resource Management - Bhenu Artha; Syakdiah; Nany Noor Kurniyati; Erna Tri Rusmala Ratnawati (Jurnal Penelitian Pendidikan IPA, 2024)
The ability to automate procedures and improve decision-making, artificial intelligence (AI) is quickly transforming a wide range of industries, including human resource management (HRM). The application of AI in different sectors, including HRM, has been predominant and profound. AI has created a disruption by displacing established HRM processes with innovative ones, and its scope includes recruitment and selection, workforce management, and learning and development. AI is enabling machines to make more accurate decisions than humans based on data and behavioral patterns. The integration of AI into HRM is changing how organizations appoint, manage, and engage their workforce, with machines taking over manual tasks and HR professionals taking on more strategic roles. This study aims to ascertain how AI affects human resource management. This research uses theoretical literature review as a research method. 22 publications serve as the research materials for this study, which employs a theoretical literature review methodology. The authors discovered that AI has an impact on HR professionals' abilities, job displacement, and position creation. AI should be used by HR managers to boost productivity.